Selection in the Introgressed Regions of the Chimpanzee Genome. (4th April 2018) - Nye, Jessica; Laayouni, Hafid; Kuhlwilm, Martin; Mondal, Mayukh; Marques-Bonet, Tomas; Bertranpetit, Jaume
Abstract: During the demographic history of the Pan clade, there has been gene-flow between species, likely >200, 000 years ago. Bonobo haplotypes in three subspecies of chimpanzee have been identified to be segregating in modern-day chimpanzee populations, suggesting that these haplotypes, with increased differentiation, may be a target of natural selection. Here, we investigate signatures of adaptive introgression within the bonobo-like haplotypes in chimpanzees using site frequency spectrum-based tests. We find evidence for subspecies-specific adaptations in introgressed regions involved with male reproduction in central chimpanzees, the immune system in eastern chimpanzees, female reproduction and the nervous system in Nigeria-Cameroon chimpanzees. Furthermore, our results indicate signatures of balancing selection in some of the putatively introgressed regions. This might be the product of long-term balancing selection resulting in a similar genomic signature as introgression, or possibly balancing selection acting on alleles reintroduced through gene flow.